2023
DOI: 10.1021/acs.orglett.3c03148
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Applications of π-Conjugation-Extended Vinyl Sulfoxonium Ylides

Sandeep Kumar,
Daksh Singh Davas,
Krishnendu Bar
et al.

Abstract: Herein, we report the synthesis of π-conjugation-extended vinyl sulfoxonium ylides from vinyl sulfoxonium ylide and electrondeficient alkynes. The new dienoate ylides are used in various transformations, such as X−H (X = S, O) insertion, halogenation, carbene-mediated transformation, and radical-mediated reductions to obtain a variety of conjugated dienoates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Between these two carbene precursors, diazo compounds react faster under metal-catalyzed conditions than sulfoxonium ylides and generate a reactive electrophilic carbene intermediate, which is then trapped by sulfoxonium ylide as a nucleophile. Prompted by this observation and our continuing interest in sulfoxonium ylides, we were intrigued to obtain stereoselective gem -difunctionalization of diazo compounds with the thiols and sulfoxonium ylides to obtain tertiary sulfide compounds, which are basic scaffolds for various natural products and medicinally important compounds. , …”
Section: Introductionmentioning
confidence: 99%
“…Between these two carbene precursors, diazo compounds react faster under metal-catalyzed conditions than sulfoxonium ylides and generate a reactive electrophilic carbene intermediate, which is then trapped by sulfoxonium ylide as a nucleophile. Prompted by this observation and our continuing interest in sulfoxonium ylides, we were intrigued to obtain stereoselective gem -difunctionalization of diazo compounds with the thiols and sulfoxonium ylides to obtain tertiary sulfide compounds, which are basic scaffolds for various natural products and medicinally important compounds. , …”
Section: Introductionmentioning
confidence: 99%
“…Biosynthetically, 6-hydroxy-2 H -chromenes are obtained via oxa-6π electrocyclization of o -quinone methides (Scheme a) . Inspired by nature’s strategy, we hypothesized that treating vinyl sulfoxonium ylide at the α-position with quinone leads to o -quinone methide that can undergo oxa-6π electrocyclization to give 6-hydroxychromenes (Scheme b). One of the main challenges in achieving the objective is that the vinyl sulfoxonium ylide can undergo classical cyclopropanation with 1,4-naphthoquinone .…”
mentioning
confidence: 99%
“…In continuation to our research interest in vinyl sulfoxonium ylides, 5 our group very recently reported that the addition of sulfoxonium ylides on ynoates produced dienyl sulfoxonium ylide, which is electronically similar to the aminodiene intermediate in the synthesis of pyridine. 6 We envisioned that, similar to the Bohlmann−Rahtz approach, in situ-generated dienyl sulfoxonium ylides can undergo intramolecular annulation to generate highly substituted arene in the absence of a catalyst or additive (Scheme 1b). However, there are two main challenges for this hypothesis: (i) Contrary to Bohlmann−Rahtz synthesis, which generates imine through thermodynamically feasible amine and keto condensation, the present reaction between sulfoxonium ylide and ketone in dienyl sulfoxonium ylide can result in epoxide rather than alkene (Scheme 1b, Step-2).…”
mentioning
confidence: 99%
“…To investigate the mechanism for the [3 + 3] annulation, we performed the reaction of sulfoxonium ylide with ynone at 10 °C; the reaction yielded dienyl sulfoxonium ylide 8 which was confirmed by NMR and HRMS analysis (Scheme 4d). 6,15 This ylide 8 underwent annulation to give m-terphenyl adduct 3a at rt and gave paraben derivative 4a using TMSOTf. When we performed the reaction using keto-derived vinyl sulfoxonium ylide the reaction gave thiabenzene derivative 9.…”
mentioning
confidence: 99%
See 1 more Smart Citation